(untitled) (Journal of Advanced Research in Social Sciences, 2023)
The dominance of Western theories in an age of globalization and swift technological advances, which brought to collective consciousness manifestations of literary and artistic genres in distant geographical places that were once viewed as primitive or exotic, necessitates raising the question of comparative poetics anew. During the second half of the twentieth century, scholars such as James J.Y. Liu, Earl Miner, Stephen Owen, and Wai-lim Yip engaged in comparing Western to Eastern poetics. However, their work fell short of reaching a unifying approach to the study of world poetics. This is the gap that Alaa Abd al-Hadi, a thinker, poet and postcolonial critic, came to fill out. Abd al-Hadi’s Nucleo-genre Paradigm is universally oriented. Based on qualitative logic and Lutfi Zadeh’s fuzzy sets, it posits that there are essential elements common to various cultural manifestations of a single genre across time and space. It is these common elements, which help decide whether a certain manifestation belongs to a certain genre, that allow for cross cultural communication and understanding while respecting cultural specificities, manifested by an infinite number of aesthetic elements. Unlike the other approaches to the field of comparative poetics, Nucleo-genre Paradigm distinguishes between two levels of genre, the poetic level of production and the aesthetic level of reception, and gives primacy to reception, which is often disregarded in genre theories. In this paper, an attempt is made to evaluate the contribution of the Nucleo-genre Paradigm beyond comparative poetics.